2022
DOI: 10.1038/s41598-022-20709-3
|View full text |Cite|
|
Sign up to set email alerts
|

Influence of Huangqin Decoction on the immune function and fecal microbiome of chicks after experimental infection with Escherichia coli O78

Abstract: Huangqin Decoction (HQD), a traditional Chinese medicine formula from the Shang Han Lun written by Zhang Zhongjing, has been used in China for nearly two thousand years. According to the traditional Chinese medicine and previous literature, HQD has the effect of clearing heat, removing toxins, relieving diarrhea and pain. Therefore, HQD was used to prevent or cure many diseases, such as inflammation, diarrhea, malaria, and other acute or chronic gastrointestinal diseases. The effect of HQD, one-herb-absent HQD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…HQD is an aqueous extract of four herbal materials, Scutellariae Radix (SR, Huangqin), Paeoniae Radix Alba (PRA, Baishao), Glycyrrhiza glabra L. (GL, Gancao) and Jujubae Fructus (JF, Dazao). Modern pharmacological research has demonstrated multiple biological activities of HQD, such as anti-inflammatory [14,15] and antimicrobial properties [16], immune-modulatory effects [17], etc. The main active components of HQD include baicalin, baicalein, paeoniflorin and glycyrrhizic acid, which have been reported to have antifungal activities [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…HQD is an aqueous extract of four herbal materials, Scutellariae Radix (SR, Huangqin), Paeoniae Radix Alba (PRA, Baishao), Glycyrrhiza glabra L. (GL, Gancao) and Jujubae Fructus (JF, Dazao). Modern pharmacological research has demonstrated multiple biological activities of HQD, such as anti-inflammatory [14,15] and antimicrobial properties [16], immune-modulatory effects [17], etc. The main active components of HQD include baicalin, baicalein, paeoniflorin and glycyrrhizic acid, which have been reported to have antifungal activities [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%